Work Culture and Ultra-Processed Food Consumption Patterns Among Office Workers: A Phenomenological Qualitative Study - Dara Avindharin, Pundra (Science Publication: Journal of Public Health and Nutrition, 2025)
ABSTRACT Introduction: The purpose of this study was to explore how workplace culture influences the consumption of ultra-processed foods (UPFs) among office workers in Indonesia, considering the rising prevalence of UPF intake and its association with metabolic risks. Our goal was to fill a gap in the literature by examining contextual, cultural, and behavioral factors through a phenomenological lens. Methods: This qualitative phenomenological study was conducted over one month (September 2025) in an urban corporate office setting. Data were gathered through semi-structured in-depth interviews and focus group discussions involving a total of 18 participants. Participants provided written informed consent. Results: The study's main findings revealed three primary themes: (1) structural time pressure reinforcing reliance on UPFs, (2) workplace social norms that normalize processed food consumption, and (3) internal negotiation between practicality and health concerns. Additional findings included emotional comfort-seeking through UPF snacks during stressful workloads. Conclusion: By highlighting sociocultural and organizational determinants of UPF consumption, this work advances understanding of occupational health behavior. This study sheds light on the broader implications for workplace nutrition interventions. Future studies should examine longitudinal changes and test multilevel intervention models. Keywords: Ultra Processed Foods; Work culture; Office workers; Qualitative study; Phenomenology.